Differences in Vegetative, Productive, and Physiological Behaviors in Actinidia chinensis Plants, cv. Gold 3, as A Function of Cane Type - Gregorio Gullo; Simone Barbera; Antonino Cannizzaro; Manuel Scarano; Francesco Larocca; Valentino Branca; Antonio Dattola (Plants)
This study investigated the influence of cane diameter on vegetative, productive, and physiological behaviors in Actinidia chinensis, cv. Gold 3. Conducted over two years (2021–2022), the experiment compared canes with larger (HD) and smaller (LD) proximal diameters. This research focused on parameters such as shoot morphology, leaf gas exchange, fruit quality, and hydraulic resistance. The results revealed that HD canes promoted more vigorous growth, with a higher proportion of long and medium shoots, whereas LD canes resulted in shorter shoots. Additionally, the HD canes demonstrated a higher leaf area and more extensive leaf coverage, contributing to enhanced photosynthetic activity, as evidenced by enhanced gas exchange, stomatal conductance, and transpiration rates. This higher photosynthetic efficiency in HD canes resulted in more rapid fruit growth, with a larger fruit size and weight, particularly in fruits from non-terminate shoots. By contrast, fruits on LD canes exhibited slower growth, particularly in terms of fresh weight and dry matter accumulation. Despite these differences, maturation indices, including soluble solids and acidity levels, were not significantly affected by cane type. The findings suggest that selecting HD canes during winter pruning could lead to earlier harvests, with improved fruit quality and productivity, making this practice beneficial for optimizing vineyard management in Actinidia chinensis.